The Implementation of Cool Japan Strategy during Covid-19 Pandemic - Salsabila, Nahda; Akbar, Ibda Khaliq Bijitama (Journal of International and Local Studies, 2023)
Abstract: The 2020 global pandemic did a significant blow to creative industries worldwide, including animation production industries. Japan as one of the most prominent players in animation industries, with its popular animation style called anime, also suffered from the pandemic. This study aims to analyze the influence of the Cool Japan Strategy to Japan anime industry before and after the Covid 19 pandemic. This research uses the qualitative method of review and read with literature study. The results show that the Cool Japan Strategy has a significant influence on the development of the anime industry, especially in terms of marketing and promotion. However, the COVID-19 pandemic also had a significant impact on the anime industry, with a decrease in revenue and changes in consumer behavior. Nonetheless, Cool Japan Strategy helps the anime industry to adapt to these changes, especially through the use of digital technology. In conclusion, Cool Japan Strategy has an important role in promoting the anime industry, and the ability to adapt to difficult environmental changes such as the pandemic can help the anime industry to continue to thrive in the future. Keywords: Cool Japan Strategy, anime industry, COVID-19, pandemic, popular culture